Postmenopausal dysgerminoma: unveiling a rare ovarian tumour a case report and review of literature - Yadav, Sneh; Sharma, Rageshwari; Kalra, Irene; Jaiswal, Deepshikha; Gaikwad, Pradip (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Ovarian germ cell tumours (OGCTs) account for 2-5% of ovarian malignancies with an annual incidence of 1:100000 and typically occurs in young women and adolescents. A pure ovarian dysgerminoma in a postmenopausal female is a rare phenomenon. We report a case of 48-year-old female postmenopausal since 3 years presented to gynaecology opd with pain lower abdomen. On clinical examination an abdominopelvic mass enlarged to 18-20-week gravid uterus size. All tumour markers were normal except lactate dehydrogenase raised to 1375. On imaging a well-defined large solid cystic heterogenous mass arising from left adnexa, suggestive of neoplastic etiology. Staging laparotomy done. A final diagnosis of ovarian dysgerminoma was made on histopathological examination.